Rational use of watershed resources in the Agreste region of the state of Pernambuco - Brazil | Uso racional de recursos em microbacia na região Agreste do estado de Pernambuco - Brasil - Reis, Ricardo Malta Gondim; Reis, Jurandir Gondim; Rolim Neto, Fernando Cartaxo; Silva, Suellen Roberta Vasconcelos da; Parahyba, Roberto da Boa Viagem; Rolim, Stela Maria Torres de Melo (Revista Geama, 2016)
It was used a model of development based on the availability of natural resources, to identify the possible options for income generation in the area, and the current infrastructure conditions and of labor qualification. It was drafted a plan to use the watershed centered in man, with the primary concern of protecting the environment of which it is part. This study aimed to establish a development plan, promoting the improvement of quality of life and control of damage to the environment in the watershed of Várzea Grande, located in the city of Belo Jardim - PE. Planning for sustainable use of a basin should involve human and natural resources available, in addition to promoting social welfare and environmental protection. In semi-arid regions occur locations at high altitudes, with less risk of crop loss, representing potential for sustained food production. The planning had as supports an expeditious survey of natural resources, classifications made on the land and socio economic information gathered in the area. It was concluded that in addition to agriculture, there should be encouragement for other activities such as domestic agribusiness, for crafts and even for rural tourism in order to increase earnings and put the population in the market economy.